Solid Flow in the Annulus of a Spouted Bed with a Flat Base - Shibata, Toshiharu; Itoh, Hironori; Uemaki, Osamu; Tsuji, Toshiro; Hirose, Masakazu (KAGAKU KOGAKU RONBUNSHU, 1997)
To determine whether the particle flow from annulus to spout in a spouted bed occurs only at the bottom or in the entire bed, the particle flow rates in the annulus of a spouted bed with a flat base were measured using an optical fiber probe. As a result, it is shown that the particle flow rate from annulus to spout at the bottom of the flat base bed is larger than that of the conical base bed, and the flow in the upper region also exists and can not be ignored when the gas velocity is increased.